Business ethics and ethical investing: from historical, ethical approach to real investments - Teresiene, Deimante; Budriene, Daiva (Technium Social Sciences Journal, 2021)
Business ethics are nowadays widely considered as an integral part of organizations. The field of business ethics addresses ethical issues between organizations and the public, examines moral business requirements, principles of justice, boundaries of integrity, moral obligations, privilege assignment, and so on. This article analyses historical issues of business ethics and focuses on ethical investment problematic. Using the historical and theoretical approach, we are trying to evaluate the development of business ethics. With the help of technical analysis indicators and standard deviation, we try to compare the trends of ethical investments and ordinary investments in the stock market during different crises.